2011
DOI: 10.1007/s00167-011-1747-y
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic treatment of localized pigmented villonodular synovitis of the knee

Abstract: Arthroscopy is a safe and effective procedure for the treatment of localized pigmented villonodular synovitis of the knee. Magnetic resonance imaging is essential to diagnose this pathologic condition and to define accurately its localization and treatment strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 25 publications
(43 reference statements)
0
31
1
Order By: Relevance
“…Mean follow-up of approximately six years (range 1-31) was longer when compared with the majority of previously published reports [3,19,23,29,31,32]. Together with the relatively high recurrence rates in this study (58-77 % after arthroscopic and 36-64 % after open synovectomy), this may indicate that to date, an underestimate of the true local recurrence rate of PVNS has been published.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Mean follow-up of approximately six years (range 1-31) was longer when compared with the majority of previously published reports [3,19,23,29,31,32]. Together with the relatively high recurrence rates in this study (58-77 % after arthroscopic and 36-64 % after open synovectomy), this may indicate that to date, an underestimate of the true local recurrence rate of PVNS has been published.…”
Section: Discussioncontrasting
confidence: 47%
“…Functional results after surgical treatment for PVNS have been reported (Table 5) [3,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], but comparison is difficult, as functional results were not specified for diffuse and localized disease, type of surgery, primary or recurrent disease and different localizations. In this study, there was no difference in functional outcome and QOL between patients who underwent primary arthroscopic or open synovectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Our follow-up data showed a higher disease recurrence rate for open surgical arthrotomy than for arthroscopic procedures. We believe that this occurred because some lesions in the mini spaces in the involved joints could be excised via arthroscopy but not via arthrotomy [10].…”
Section: Discussionmentioning
confidence: 99%
“…There is currently no consensus on optimal treatment of localised PVNS, but it is generally accepted that arthroscopic excision often results in successful treatment 13. As localised PVNS is a rare disorder, the recurrence frequency has not been definitively established; however, a review of long-term follow-up studies on arthroscopically treated localised PVNS by Dines et al 16 reported no recurrences in patients followed for up to 4.5 years postoperatively, hinting that arthroscopic treatment alone might be sufficient.…”
Section: Discussionmentioning
confidence: 99%